Piriformis Syndrome: diagnosis and treatment - Tanveer, Fahad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Piriformis Syndrome (PS) also correlates with the other medical diseases during the outlook of the syndrome in the clinical settings, because it may be similar to primary sacral dysfunction, lumbarradiculopathy or innominate dysfunction. For the identification of the syndrome, it needs to have the knowledge of structure and function of the piriformis muscle and its relationship with the sciatic nerve. The clinician’s review the clinical conditions and anatomical features of this condition, encapsulating the osteopathic medical approach to management and diagnosis. In holistic approach, the detail requires the examination of the neurological history of the patient which contains the pathological content of the piriformis syndrome. PS is a kind of sciatica which occurs due to a compression of the sciatic nerve by the piriformis muscle. This cause of sciatica is not very frequent but it is still significant. Its diagnosis is not easy due to overlapping of symptoms of other conditions of low back and pelvic region pain. An ultrasound-guided injection technique renders a much improved accuracy to locate the piriformis muscle. An interdisciplinary evaluation is recommended for the optimization of diagnosis and treatment approach [1]. Treatment of PS has always been focusing on physical therapy and stretching. However, the refractory patients receive anesthesia and corticosteroid injections in piriformis muscle. The use of botulinum toxin for the treatment of PS is also popular, it relieves the compression in sciatic nerve [2].